L'opposabilité aux tiers de la convention d'arbitrage - Mhaoun, Jalal (Université de Bordeaux, 2022)
Il existe en droit commun et en droit de l’arbitrage deux mécanismes similaires ayant un objectif commun : rendre l’acte juridique apte à faire sentir ses effets à l’égard des tiers. Il s’agit, pour le droit commun, du principe de l’opposabilité et, pour le droit de l’arbitrage, de la règle de l’attraction des tiers à la procédure arbitrale. Ces deux techniques, qui procèdent de la même manière et partagent presque les mêmes conditions de mise en œuvre, ont en revanche une qualification distincte. En droit commun, l’opposabilité est connue pour être un principe à part entière dont la fonction principale, la fonction de sanction, est relativement offensive, puisqu’elle oblige les tiers, sujets auxquels l’opposabilité est habituellement attachée, au devoir général de respect, à l’obligation de ne pas nier l’existence des engagements d’autrui et de ne pas y porter atteinte au risque de subir les conséquences de leur immixtion. Le principe de l’opposabilité a également une fonction probatoire qui permet aux tiers d’opposer aux parties, ou aux autres tiers, l’existence d’un contrat pour apporter la preuve d’un fait. Alors qu’en droit de l’arbitrage, la règle de l’attraction permet une extension des effets de la convention d’arbitrage à l’égard des tiers qui se trouvent impliqués positivement ou négativement, directement ou indirectement à la négociation, la formation, l’exécution ou l’anéantissement du contrat dans lequel est insérée la clause d’arbitrage.Puisque les deux techniques partagent le même procédé et agissent sur les mêmes personnes, la présente thèse a pour but d’étudier la réception du principe d’opposabilité en droit de l’arbitrage. Cette réception passe par une intégration et un attachement de la règle de l’attraction au principe de l’opposabilité comme fonction nouvelle. L'objectif principal est donc de répondre à une question précise : comment faire en sorte que le principe de l'opposabilité soit accepté et transposé en matière arbitrale pour ainsi voir à l’œuvre toutes ses fonctions, y compris celle qu’il vient d’intégrer, sans que le système juridique ne subisse de profonds bouleversements.Notre analyse de la réception se déroule en deux étapes. Après avoir rappelé et établi le cadre théorique du principe de l'opposabilité, dans lequel avons-nous examiné les différentes conceptions, justifications et sujets de l’opposabilité ; cadre qui nous a offert une image plus claire et réaliste des applications de l'opposabilité en droit commun et nous a permis de voir si ces applications et fonctions étaient en mesure de justifier la règle de l'attraction. Nous avons donc conclu que l’opposabilité est parfaitement recevable en droit de l’arbitrage à condition d’y intégrer ladite règle de l’attraction comme fonction nouvelle. Convaincus de sa réception en droit de l'arbitrage, nous avons, ensuite, soumis la nouvelle fonction d’attraction à un ultime test, celui de l’efficacité. L’examen de l’efficacité aura permis de recenser les limites de la règle de l’attraction dont nous avons proposé un certain nombre de solutions de renouvellement, et ce, dans le but de mieux intégrer la fonction et pour que celle-ci puisse avoir un impact systématisé sur le droit de l’arbitrage.
Keywords: Arbitrage; Arbitrage multipartite; Arbitragem; Arbitraje; Arbitration; Convention d'arbitrage; Extension; Opposability; Opposabilité; Règle de l'attraction; Third parties; Tiers; Tiers (droit); Transmission

Reforming investor-state dispute resolution: Focusing on the roles of domestic courts - Ma, Wanli (Erasmus University Rotterdam, 2022)
While a universally applicable multilateral agreement on investment is not yet available, a broad network of BITs and investment chapters in FTAs has been put in place to protect foreign investors and their investments. Meanwhile, investment arbitration has become a defining feature of modern international investment law over the recent decades, enabling foreign investors to launch an investment arbitration against host states, often without the need to go through local remedies before that. With the caseload of investment arbitration increasing at a rather rapid speed, such a dispute resolution method has also attracted fierce criticism. Many commentators have alleged, among other, that the decision-making of investment arbitrators has been inconsistent and unpredictable, that investment arbitration has become a threat to public interest, that investment arbitration proceedings are not transparent enough, that the arbitrators involved are not independent nor diverse enough, that the lack of an applellate mechanism compromises the quality of decision-making, and that investment arbitration has become far too costly and time-consuming. Against such a backdrop, the global community has made joint efforts to reform the investment arbitration system, not least through various initiatives developed at ICSID and UNCITRAL. Almost at the same time, national states also seem to have started to reconsider the costs and benefits of including investment arbitration in their investment agreements as a method for the resolution of disputes with foreign investors. Although the caseload of investment arbitration continues to grow and national states keep concluding IIAs containing investment arbitration clauses, at least some countries in their more recent investment treaty making practice have demonstrated a policy trend to rein in investment arbitration and ramp up the role of domestic courts in resolving investment disputes. They often do so by exiting the ICSID system, terminating their investment agreements with economic partners, excluding investment arbitration from their investment agreements, and conditioning investment arbitration upon the prior use of litigation via domestic courts. While the state practice mentioned above surely does not suggest the global society has any intention to abandon investment arbitration any time soon, it prompts us to take a step back and reconsider the role that domestic courts may play in resolving investment disputes, instead of solely focusing on the piecemeal reform of investment arbitration. When it comes to investor-state dispute resolution, domestic courts can indeed play different roles along the process. Like investment tribunals, domestic courts can also adjudicate investment disputes between foreign investors and local authorities. Such a judicial role sometimes is also confirmed in investment agreements through, for example, the exhaustion of local remedies rule, the clause demanding pursuit of local remedies prior to investment arbitration and the fork-in-the-road provision. In the context of non-ICSID arbitration, disputing parties are often entitled to applying for the review by domestic courts loci arbitri of the rulings and awards rendered by investment tribunals. Domestic courts loci arbitri would thus assume a supervisory role with regard to arbitration proceedings and arbitral outcomes, as they may set aside arbitration awards in question according to the review grounds enumerated in local arbitration laws. Moreover, domestic courts in a broader sense may be called upon to support the conduct and / or authority of investment arbitration, by recognizing and enforcing the investment awards rendered by arbitral tribunals and issuing interim measures of a judicial nature to facilitate the arbitration process. Since litigation through domestic courts and investment arbitration are two primary remedies that foreign investors often rely on for the resolution of investment disputes, this study constructs three models of institutional design with regard to the allocation of jurisdiction over investment disputes between domestic courts and investment tribunals. While the reality may turn out to be more complicated, such three models roughly represent the institutional choices facing national states. These three models are: (i) utter reliance on domestic courts as the exclusive forum for investor-state dispute resolution, (ii) investment arbitration operating as a substitute for litigation via domestic courts, and (iii) investment arbitration working as a complement to litigation via domestic courts. In order to conduct a comparative institutional analysis of the three models to reveal their respective tradeoffs, this study employs a goal based approach which is increasingly used to analyze the effectiveness of international adjudicatory mechanisms. As a result of the employment of the goal-based approach, the goals of investor-state dispute resolution are recognized as achieving fair and efficient dispute resolution, promoting state compliance with investment treaty norms, facilitating the objectives of the investment law regime, and legitimizing the underlying investment treaty regime. While the quality of the national judiciaries of many developing countries is not the same as it was decades ago largely due to the judicial reforms launched around the world, fairness and efficiency in dispute resolution still cannot be fully guaranteed in the domestic courts of those countries without a robust legal system and a good record of the rule of law. However, there are certain institutional characteristics of court litigation that may facilitate the efficiency in the resolution of investment disputes, such as the unique advantage of domestic courts that they can work as a single forum for dispute resolution and the better knowledge of court judges of the domestic legal framework at issue. Domestic courts also hold great potential in promoting the compliance by national states with investment treaty norms not least because they have more flexibility in awarding both primary and secondary remedies, but that of course depends on whether domestic courts can adjudicate investment disputes in a fair and impartial manner. Moreover, while utter reliance on litigation via domestic courts may strengthen the domestic rule of law and improve the investment climate in the long term by pressing host states to improve their legal systems and judicial institutions, it may also invite the politicization of investment disputes and the diplomatic intervention from home states in investor-state dispute resolution. Furthermore, despite the risks created for foreign investors, reliance on domestic courts as the exclusive forum may enhance the legitimacy of the investment treaty regime by reducing the sovereignty costs incurred by national states and putting domestic investors and foreign investors on the same footing. Investment arbitration operating as a substitute for domestic courts, on the other hand, demonstrates certain advantages, which are typically affiliated with international arbitration, in achieving the fair and efficient resolution of investment disputes. Unlike domestic courts, which are an integral part of the state apparatus, investment arbitrators are often immune from the influence of domestic politics and are thus believed to be independent and impartial. Meanwhile, the specialization of arbitrators in a particular area of knowledge and the procedural flexibility of arbitration proceedings, among others, are expected to improve efficiency in the resolution of investment disputes. However, empirical evidence presented in the literature sometimes suggests that, in reality, investment arbitrators may not be that unbiased and investment arbitration proceedings often drag on with a bill of a massive amount. Besides, although investment tribunals have a broad scope of jurisdiction over the behavior of different government branches, the practical difficulties they face in awarding primary remedies may damage their ability in promoting state compliance with investment treaty norms. In addition, the introduction of investment arbitration grants to foreign investors a standing in international arbitration proceedings, to a large extent reducing the need for diplomatic protection and home state intervention. However, the positive impact of investment arbitration in facilitating the development of the domestic rule of law and the maintenance and increase of foreign capital is less certain. As for the preservation of the legitimacy of the underlying investment treaty regime, investment arbitration as an alternative to domestic courts cannot be relied on to produce much positive impact. For instance, the increasing sovereignty costs and financial burden imposed on national states would probably prompt more of them to turn against the investment treaty regime. The complement model, in which domestic courts assumes primary jurisdiction and investment tribunals secondary jurisdiction over investment disputes, stands a good chance in keeping the advantages of both court litigation and investment arbitration while avoiding their disadvantages. In the complement model, domestic courts will act as the first line of defense in adjudicating investment disputes, and the institutional advantages of court litigation will be enabled to release their potential. At the same time, even if foreign investors are not satisfied with the judicial outcome or regard the court proceedings as corrupt or unfair, they may escalate the specific disputes to investment tribunals for further consideration. Since court judges are more knowledgeable and experienced in the interpretation and application of domestic law, the legal analysis of court judges will also benefit the decision-making of investment arbitrators in the subsequent arbitration proceeding. Allowing domestic courts to have a first try at investment disputes will also increase the likelihood that primary remedies could be accorded, thus the unique advantages of primary remedies in promoting state compliance with investment treaty norms are not discarded in the complement model. Moreover, the complement model is also more promising in facilitating the achievement of the objectives of the investment treaty regime, and that is because domestic courts are not marginalized in the complement model, the antagonism between foreign investors and host states may be expected to decrease, and the depolicization of investment disputes will not be lost since investment arbitration is kept as an option. Furthermore, the complement model strikes a better balance among the interests of foreign investors, host states and other stakeholders, thus it is more likely to preserve and even enhance the legitimacy of the underlying investment treaty regime than the other two institutional choices. Although the complement model serves the goals of investor-state dispute resolution the best in theory, not any casual combination of court litigation and investment arbitration will do the job; instead, only a smart mix of the two dispute resolution methods can give full play to the advantages of the complement model. Now, we switch to the supervisory role of domestic courts in investor-state dispute resolution. While a systemic appellate mechanism has not been created for investment arbitration, disputing parties may rely on setting-aside proceedings in non-ICSID arbitration to challenge arbitration awards. In other words, domestic courts loci arbitri may conduct a judicial review of the rulings and awards made by investment tribunals. However, a theoretical analysis of the judicial review mechanism supported by empirical evidence has shown that the mechanism has several flaws, which include but are not limited to the points that follow immediately. Since there is only a casual link between the seat of arbitration and the investment dispute, it is inappropriate to subject the decision-making of arbitrators to the judges from the place where the arbitration proceedings took place. The very fact that review courts have been overwhelmingly located within the developed North could raise concern that the judicial review mechanism is inherently biased against developing countries which have already shown a somewhat negative sentiment towards investment arbitration. Given that judicial review proceedings could easily go through more than one instance of court proceedings in many jurisdictions, the dispute resolution process may consume more time and generate higher costs. From this point of view, the judicial review mechanism favors the richer party in investment arbitration and could become a weapon of dilatory tactics available for such a party. Considering the higher error costs relating to investment arbitration than that relating to commercial arbitration, limited review grounds and a copious amount of deference to arbitral tribunals may not prove to be as effective in the scrutiny of investment awards. Moreover, the idiosyncrasies as to review grounds and standards across jurisdictions indicate that inconsistency would also probably permeate the judicial review practices, which would then encourage forum shopping that leads to increased costs and decreased efficiency. In addition, as both review courts and enforcement courts may exercise control over investment awards, the setting-aside decision may be merely disregarded at the enforcement stage and the overall efficiency of investor-state dispute resolution may be reduced. In order to overcome many of the flaws mentioned above, a delocalized form of review should be introduced to take place of the current judicial review mechanism.

La convention d’arbitrage : étude comparée de droit franco-marocain - Ajouby, Samia (Université Paris 2, 2022)
Terre attractive pour les investisseurs étrangers, le Maroc voit son économie muter au gré de l'implantation d'entreprises. Face à cette situation, l'adaptation du droit est essentielle. Il s'agit effectivement d'un instrument fondamental pouvant être mis à la disposition des entreprises pour leur offrir un cadre légal rassurant quant à la prospérité de leurs intérêts. Or la justice étatique inspire traditionnellement la crainte du fait de sa lourdeur administrative et de son incapacité à assurer des garanties procédurales suffisantes Pour résorber cela, le législateur marocain a tendu à développer les modes alternatifs de règlement des conflits, tel que l'arbitrage. C'est dans ce contexte que la loi intitulée "arbitrage et médiation conventionnelle" a été ratifiée, le 6 décembre 2007. Elle s'inspire du droit français pour modifier les articles 306 à 327 du Code de procédure civile marocain. Ce cadre procédural vise à insuffler une vigueur nouvelle aux modes alternatifs de règlement des conflits. Néanmoins, la souplesse du régime a pour corollaire des pathologies qui peuvent affecter les conventions d'arbitrage. La rédaction des clauses approximatives, et la formation insuffisante de certains arbitres se traduisent par des conventions d'arbitrage bancales, sources de nouveaux problèmes là où elles devraient faciliter la résolution des litiges. Dans ces conditions, une nouvelle réforme a donné naissance à un Code de l’arbitrage, ratifié le 24 mai 2022. Il s’agira d’étudier l’évolution de la législation marocaine de l’arbitrage, dans une dimension comparatiste avec le droit français, et à la lumière d’une recherche constante de l’efficacité de la convention d’arbitrage. [Abstract] The arbitration agreement : a comparative study of French and Moroccan law : Morocco is an attractive country for foreign investors, and its economy is changing as companies are setting up. Faced with this situation, the adaptation of the law is essential. Indeed, it is a fundamental instrument that can be made available to companies to offer them a reassuring legal framework for the prosperity of their interests. However, the state justice system traditionally inspires distrust because of its administrative cumbersomeness and its inability to ensure sufficient procedural guarantees. In order to solve this, the Moroccan legislator has tended to develop alternative methods of dispute resolution, such as arbitration. It is in this context that the law entitled "arbitration and conventional mediation" was ratified on December 6, 2007. It is inspired by French law to modify articles 306 to 327 of the Moroccan Code of Civil Procedure. This procedural framework aims at breathing new life into alternative dispute resolution. Nevertheless, the flexibility of the regime has as a corollary pathologies that can affect arbitration agreements. The drafting of unprofessional clauses and the inadequate training of arbitrators result in flawed arbitration agreements, which are a source of problems where they should facilitate the resolution of disputes. In these conditions, a new reform has led to an Arbitration Code, ratified on May 24, 2022. The aim is to study the evolution of Moroccan arbitration legislation, in a comparative dimension with French law, and in the light of a constant search for the efficiency of the arbitration agreement.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Comparative law; Contentieux international; Contract law; Contrats; Convention d'arbitrage; Conventions d'arbitrage international - Maroc; Dispute resolution; Droit comparé; Droit des contrats; Droit international; Efficacité; Efficiency; France; International law; International litigation; Maroc; Modes alternatifs; Procedure; Procédure; Règlement de conflits; Résolution des litiges

Processo arbitral: a estabilização da demanda - Leão, Fernanda de Gouvêa (Universidade de São Paulo, 2022)
Esta tese trata da estabilização da demanda no processo arbitral. Ao se falar da estabilização da demanda no processo arbitral, são muito comuns as afirmações de que, no processo arbitral, o tratamento é diferente, pois é mais flexível. Também, comumente se afirma que a estabilização da demanda na arbitragem se daria no momento de assinatura do termo de arbitragem. No entanto, entende-se que o tema não foi analisado de forma aprofundada, e, inclusive, com base nas pesquisas realizadas, poucas foram as obras nacionais que trataram especificamente da estabilização da demanda arbitral. Diante disso, este trabalho buscará analisar como se dá a estabilização da demanda no processo arbitral e as hipóteses de modificação da demanda no decorrer do processo. Para tanto, inicialmente serão apresentadas considerações iniciais, necessárias ao desenvolvimento do trabalho, como a natureza jurídica da arbitragem e sua inclusão na teoria geral do processo. Após, analisa-se o processo arbitral, a formação da demanda na arbitragem e como se dá a definição das regras a serem observadas no processo arbitral, e como são definidos os poderes jurisdicionais dos árbitros. Ainda, ao se falar de estabilização da demanda, necessariamente deve ser estudado o conteúdo da demanda arbitral e sua individualização, ou seja, o que constitui o objeto litigioso do processo arbitral. Em seguida, será feita a investigação de quais são os elementos da demanda arbitral, as teorias que tratam de cada um deles e qual deve ser seu conteúdo mínimo. Ultrapassada essa investigação e fixados os conceitos necessários ao desenvolvimento do tema, serão analisadas as linhas gerais da estabilização da demanda, sua natureza jurídica e os fundamentos que embasam não só a regra da estabilização da demanda, mas também sua mitigação, do que decorre da análise dos sistemas rígidos e flexíveis. Definidos os conceitos gerais acerca da estabilização da demanda arbitral, analisaremos como outros ordenamentos tratam da questão, bem como as disposições no processo estatal brasileiro, para que se possa compreender o que o sistema processual entende como estabilização da demanda e as hipóteses de mitigação. Em seguida, trataremos do momento de estabilização da demanda arbitral, possibilidade de modificação dos elementos da demanda e consequências da violação da regra da estabilização da demanda. Por fim, todo estudo teórico deve mostrar seu viés prático, de modo que as análises que foram feitas possam ser aplicadas pelas partes e pelo árbitro. Por essa razão, o último capítulo é dedicado às recomendações sobre o tratamento da estabilização da demanda na arbitragem. This thesis addresses the stabilization of demand in the arbitral procedure. When discussing the demand stabilization in the arbitration procedure, it is widely asserted that in the arbitration proceeding the treatment is different since it is more flexible. Furthermore, it is commonly stated that the stabilization of demand in arbitration would occur when the terms of reference are signed. Nevertheless, it is understood that the issue has not been analyzed comprehensively and, based on the research conducted, few Brazilian studies have specifically addressed the stabilization of the arbitral demand. Thus, this study will analyze how the stabilization of the demand occurs in the arbitration procedure and the hypotheses of modification of the claim in the course of the procedure. For this purpose, the necessary initial considerations for the development of the study will be presented, such as the legal nature of arbitration and its inclusion in the general theory of procedure. After that, we will analyze the arbitration process, the formation of the demand in arbitration, and how the rules to be observed in the arbitration process are defined, as well as the jurisdictional powers of the arbitrators. Afterward, we will then proceed to the analysis of the arbitration process, the constitution of the demand in arbitration, and how the rules to be observed in the arbitration procedure are defined, as well as how the jurisdictional powers of the arbitrators are defined. Moreover, when discussing the stabilization of the demand, one must necessarily study the content of the arbitration claim and its individualization, i.e., what constitutes the litigious object of the arbitration procedure. Following that, an investigation of the elements of the arbitration claim, the theories that deal with each of them, and what the minimum content should be, will be carried out. Once this investigation has been concluded and the concepts necessary for the development of this thesis have been established, the general lines of the stabilization of demand will be analyzed, as well as its legal nature and grounds that support, not only the rule of stabilization of demand, but also its mitigation, which follows from the analysis of rigid and flexible systems. Once the general concepts concerning the stabilization of arbitral demand are defined, we will analyze how other legal systems address the issue, as well as the provisions in the Brazilian state process, so that we can comprehend what the procedural system understands as stabilization of demand and the hypotheses of mitigation. Next, we will address the moment of stabilization of the arbitral demand, the possibility of modifying the elements of the claim and the consequences of the violation of the rule of stabilization of demand. Finally, every theoretical study must reveal its practical side, so that the analyses that have been made can be applied by the parties and the arbitrator. For this reason, the last chapter is devoted to recommendations on the treatment of demand stabilization in arbitration.
Keywords: Alemanha; Arbitrage; Arbitragem; Arbitration; Arbitration procedure; Brasil; Direito Comparado; Direito Processual Civil; Espanha; Estados Unidos; Juízo arbitral; Litígio; Modification of the elements of the demand; Portugal; Procedimento especial; Stabilization of the demand

Desconsideração da personalidade jurídica na arbitragem - Ferraz, Renato de Toledo Piza (Universidade de São Paulo, 2022)
A presente tese se ocupa de analisar a possibilidade de vinculação de não signatário da convenção de arbitragem ao processo de jurisdição privada via desconsideração da personalidade jurídica no âmbito de arbitragens domésticas. Para tanto, no Capítulo 1, examinam-se premissas teóricas ligadas ao processo de aquisição da personalidade jurídica; de como ele opera limitando a responsabilidade dos integrantes do ente personalizado; e do embate entre autonomia da atividade societária e abuso de direito do qual pode resultar a desconsideração da personalidade jurídica. A teoria desconstitutiva é verificada desde sua criação até os dias atuais, enfatizando-se seu modo de funcionamento à luz dos pressupostos que autorizam sua incidência e os efeitos que se seguem desse reconhecimento segundo a concepção clássica da técnica desconstitutiva. No Capítulo 2, aborda-se o papel da autonomia da vontade para a teoria geral dos contratos e para a arbitragem, apontando-se o alcance e a classificação desta última para, a seguir, adentrar no tema da verificação do consentimento para arbitrar conflitos. Nesse contexto, são analisadas diversas teorias que fundamentam a participação de parte não signatária em arbitragens para se chegar à formulação daquilo que se denominou de consentimento suficiente para arbitrar conflitos. Ao ensejo do estudo das diversas teorias que embasam a extensão da cláusula compromissória, procura-se assinalar distinções, mas também semelhanças, que tornem viável apropriar seus argumentos, quando for o caso, para a específica hipótese de vinculação de terceiro via desconsideração da personalidade jurídica. No Capítulo 3, o epicentro da tese, são investigados os fundamentos que, segundo se defende, autorizam a hipótese. Para tanto, são levados em consideração implicações próprias da natureza jurídica da arbitragem e da regra do kompetenz-kompetenz; a equiparação entre árbitros e juízes togados no exercício de suas funções; o valor da efetividade para a jurisdição arbitral, com foco na análise econômica do direito e no impacto para os custos transacionais da arbitragem ao se rechaçar a hipótese defendida; a boa-fé objetiva como meio apto a identificar o consentimento suficiente; e, finalmente, uma análise individual de alguns trabalhos doutrinários que defendem a hipótese contrária, expondo criticamente seus motivos. Como resultado dos pontos abordados, procura-se responder se a análise da pretensão desconstitutiva por árbitros choca-se com o sistema por alargar os limites da convenção, seja em razão da matéria, seja em virtude dos sujeitos contratantes do pacto arbitral. A conclusão a que se chega é no sentido de que a conjugação desses fatores possibilita a vinculação de parte não signatária ao processo arbitral em razão da utilização abusiva da personalidade jurídica, sendo essa a solução mais consentânea com os propósitos da técnica desconstitutiva estampada no art. 50 do CC e conforme o que dispõe o sistema arbitral. This thesis is dedicated to analyzing the possibility of binding a non-signatory of the arbitration agreement to the private jurisdiction process via disregard doctrine in domestic arbitrations. To this end, Chapter 1 analyzes the theoretical premises linked to the process of acquisition of legal entity, the way it operates in limiting the liability of the members of the personalized entity, and the conflict between the autonomy of the companys activity and abuse of rights, which may result in the disregard of legal entity. The disregard doctrine is verified from its conception to the present days, emphasizing the way it works according to the requirements that allows its incidence and the effects from its recognition according to the classic doctrine of the corporate veil. Chapter 2 deals with the role of autonomy of the will in the general theory of contracts and arbitration, pointing out the reach and classification of the arbitration to then go into the theme of the verification of consent to arbitrate conflicts. In this context, the various theories that support the participation of a non-signatory party in arbitration proceedings are analyzed to formulate what is called "sufficient consent" to arbitrate disputes. In the course of analyzing the various theories on which the extension of the arbitration clause is based, an effort is made to point out distinctions as well as similarities that could make feasible to adopt their arguments, where appropriate, for the specific hypothesis of binding a third party through vail of legal entity. In Chapter 3, the epicenter of the thesis, the grounds by which, according to what has been defended, the arguments that authorizes the hypothesis are examined. To this end, the implications of the legal nature of arbitration are taken into consideration; the rule of kompetenz-kompetenz; the equivalence between arbitrators and judges in the exercise of their functions; the value of effectiveness for the arbitral jurisdiction, focused on the Economic Analysis of Law and the impact on the transactional costs of arbitration when the defended hypothesis is rejected; objective good faith as liable ground for identifying sufficient consent; and finally, individual analysis of some doctrinal works defending the contrary hypothesis, critically exposing their motives. As a result of all the points analyzed, an attempt is made to answer whether the analysis of the unconstitutional claim by arbitrators clashes with the system by extending the limits of the arbitration convention, whether due to the subject matter or to the contracting parties of the arbitration agreement. The conclusion is that the combination of these factors allows the binding of the non-signatory party to the arbitration process due to the abusive use of the legal entity, being this the most consistent solution with the purposes of the unconstitutional technique stamped in article 50 of Brazilian Civil Code and according to what the arbitration system disposes of.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Arbitration Law; Arbitration clause; Binding of non-signatories; Civil procedural law; Cláusula compromissória arbitral; Convenção de arbitragem; Direito arbitral; Direito processual civil; Limites subjetivos; Personalidade jurídica; Subjective limits; Vail of legal entity; Vinculação de não signatários

L'efficacité des mesures provisoires et conservatoires dans l'arbitrage interne : étude du droit français et du droit koweïtien - Alenezi, Ali (Université Jean Moulin Lyon 3, 2022)
En droits français et koweïtien, il existe une juridiction de référé quelque soit la matière. Cette juridiction a le pouvoir de prendre des mesures provisoires et/ou conservatoires pour régler momentanément une situation urgente ou pour sauvegarder provisoirement et rapidement un droit dans l’attente qu’un jugement au fond soit rendu. Toutefois, en matière arbitrale, le juge étatique n’est pas le seul compétent pour pouvoir prendre lesdites mesures. En effet, l’arbitre désigné dans la convention d’arbitrage dispose également de cette prérogative. À ce titre, les juges étatiques ou arbitraux français et koweitiens, bénéficient de points forts mais également de faiblesses lorsqu’ils rendent ces mesures. D’une part, les juges des référés français et koweïtiens disposent de toutes les prérogatives permettant de rendre leurs décisions provisoires d’une manière efficace et rapide. Toutefois, la lourdeur des règles procédurales applicables devant les juridictions de référé peut s’avérer dissuasif. Elles peuvent ainsi préférer se tourner vers l’arbitre puisque les règles de procédure propre à l’arbitrage sont souvent perçues comme étant modernes, simples et rapides. Toutefois, les arbitres de ces deux États ne disposent pas de l’impérium, qui garante garantissant l’efficacité et l’effectivité de leurs mesures. À ce titre, la substance de cette thèse résidera dans la comparaison entre le juge des référés et les arbitres français et koweitiens concernant l’efficacité et la célérité de leurs mesures provisoires et/ou conservatoires. La présente thèse s’attachera à démontrer, au travers de cette comparaison, que l’arbitrage est préférable au traitement du litige malgré l’absence de certaines prérogatives importantes qui aident les arbitres pour rendre leurs mesures provisoires et/ou conservatoires rapides et efficaces. In French and Kuwaiti national courts, the power of urgency exists regardless of the nature of the courts, civil or commercial. The power of urgency entitles to grant all provisional and precautional orders to address an emergency situation or to preserve the right of the parties without prejudice to the origin of the substantive right. However, in the case of an existence of an arbitration agreement, the judge does not have the right to grant these orders solely. In fact, the arbitrator appointed in the arbitration agreement also has the right to this privilege. In this regard, every French and Kuwaiti judge whether an arbitrator or a national judge has points of strength and weakness when granting these orders. On one hand, the French and Kuwaiti national judge has all the privileges that entitle them to grant provisional and precautional orders effectively and quickly. However, the nature of the procedures used to grant these orders can sometimes be stressful and exhausting to the parties involved in a way that affects the speed and effectiveness of these orders. On the other hand, the procedures followed before the arbitrators are easy, fast, and effective, but the arbitrators do not have the power to redress to ensure the execution of these orders, which affects the administration of justice. Therefore, the essence of this study lies in the comparison between the national judge and the arbitrator, French and Kuwaiti, in terms of the effectiveness and the speed of granting provisional and precautional orders. This study shows that arbitration is always preferred by disputants to obtain provisional and precautional orders more quickly and effectively than national courts.
Keywords: Arbitrage; Arbitral proceedings; Arbitration; Arbitrator; Arbitrator privileges; Arbitre; Astreintes; Célérité et efficacité des mesures provisoires et/ou conservatoires; Droits français et koweïtien; Imperium; Judicial expedited proceedings; Juge des référés; Mesures provisoires et/ou conservatoires; Pouvoir coercitif; Pouvoirs de l'arbitre; Pouvoirs du juge des référés; Référé arbitral et judiciaire; The French and Kuwaiti Laws; The power of redress; The provisional and precautional orders; The speed and effectiveness of provisional and precautional orders; Threatening fines; Urgent judge

La mise en question de l’arbitrage d’investissement et la réforme du règlement des différends entre investisseurs et États - Sucharitkul, Vanina (Université Paris 2, 2022)
Au cours des dernières décennies, le régime de règlement des différends entre investisseurs et États (« RDIE »), par le biais de l’arbitrage ad hoc, a été l’objet d’un examen approfondi et de critiques croissantes. Au fur et à mesure que les États défendeurs de diverses régions ont perdu des affaires d’arbitrage d’investissement, ils ont été comme désenchantés par ce type de mécanisme de résolution des litiges, dans ce qui est désormais connu comme le contrecoup de l’arbitrage d’investissement. Plus récemment, ces critiques se sont intensifiées au point que l’Union Européen a remplacé le RDIE contemporain par une cour permanente d’investissement pour régler ces différends. Une approche intermédiaire de la réforme du système par l’établissement d’un organe d’appel visant à donner de la cohérence aux nombreuses sentences arbitrales ad hoc est également envisagée. Cette thèse analyse les principales critiques du système du RDIE actuel afin d’examiner sa pertinence et effectue une comparaison entre les options de réforme, la manière dont elles sont censées résoudre les défauts du système, ainsi que les implications découlant de certaines des solutions les plus débattues. L’objectif de la thèse est de faire valoir qu’une refonte radicale ou révolutionnaire du système d’arbitrage des investissements ne fera que générer des incertitudes, susciter des problèmes juridiques et pratiques très complexes, et ne n’apportera finalement pas de meilleurs résultats. L’accent devrait plutôt être mis sur une indispensable évolution ou réforme substantielle au niveau des traités, afin de tirer les leçons des cas passés et de s’assurer que la rédaction des traités répond mieux aux défis actuels. = The dispute settlement regime between investors and States through ad hoc arbitration has come under heavy scrutiny and mounting criticism in the past few decades. As respondent States in various regions have lost investment arbitration cases, those States have become disenchanted with this form of dispute resolution mechanism in what has become known as the backlash against investment arbitration. More recently, these critiques have escalated to the extent that the European Union has replaced it with a completely new scheme that includes dismantling the investment arbitration system by replacing it with a permanent investment court to settle such disputes in its trade agreement. An intermediate approach to reforming the system, the establishment of an appellate body aimed at providing consistency to the numerous ad hoc arbitration awards, is also being considered. This thesis analyses the main criticisms of the current investor-State dispute settlement (“ISDS”) system to determine its validity and carries out a comparison between the policy reform options, how they are intended to solve the system’s purported flaws, as well as the implications arising from some of the hotly debated options. The aim of the thesis is to argue that drastic overhaul or revolutionary reform to the investment arbitration system will only lead to uncertainties, more complex legal and practical problems and would not yield better results. Instead, the focus should be on the evolution of substantive reform at the treaty level, to address the lessons learned from past cases and ensure that treaty drafting responds to current day challenges.
Keywords: Appellate Mechanism; Arbitrage; Arbitrage international; Arbitragem; Arbitration; Convention CIRDI; Cour Multilatérale d’Investissement; Droit et État; Groupe de travail III de la CNUDCI; ICSID Convention; INVESTMENTS; ISDS; ISDS Reform; Incohérence de sentences arbitrales; Inconsistent Arbitral Awards; Investissements étrangers (droit international); Investisseurs et État; Investment Court System; Investor-State Dispute Settlement; Multilateral Investment Court; Mécanisme d’appel; RDIE; Règlement des différends; Règles de transparence; Réforme du RDIE; Système de Cour d’Investissement; Transparency Rules; UNCITRAL Working Group III

La négociation dans le règlement des litiges internationaux d'investissement - Paredes Balladares, Francisco Xavier (Université Paris 1, 2022)
La négociation est une institution fascinante du droit de l’investissement, polyvalente et multifonctionnelle. L’étude systématisée de la négociation dans le droit de l’investissement fait ressortir que cette institution est plus qu’un simple moyen permettant de parvenir à des accords. En réalité, la négociation est partout dans le droit de l’investissement. Il s’agit de la seule institution véritablement transversale au droit des investissements, qui intervient de nombreuses manières dans les rapports entre les investisseurs et les États d’accueil. Nous pouvons attester de l’existence des négociations avec la négociation des accords internationaux d’investissement ou de contrats d’investissement entre l’État d’accueil et l’investisseur. De surcroît, la négociation est un instrument au service de l’instance juridictionnelle qui sert aux arbitres dans l’interprétation des accords ainsi que pour la détermination de la responsabilité des parties. Si les divers rôles de la négociation dans le droit de l’investissement ont fortement contribué à l’évolution du droit international, la négociation reste une institution peu connue. Sa nature, sa portée, et son contenu juridique restent peu étudiés et non systématisés dans le droit de l’investissement. De ce fait, cette recherche offre une analyse approfondie de la négociation afin de trouver sa place dans l’ordre juridique de l’investissement (en général) et dans le règlement des litiges (en particulier). Nous examinerons dans cette recherche les nombreux apports de la négociation au droit de l’investissement permettant d’affirmer que la négociation constitue le mécanisme essentiel dans la conclusion des accords ; qu’elle impose aux parties des comportements précis ; qu’elle est un instrument qui permet aux tribunaux internationaux de déterminer la responsabilité des parties en fonction de leurs actions et inactions ; enfin, qu'elle constitue un instrument qui aide la justice arbitrale à interpréter les accords ponctuels. Ainsi, cette recherche a pour ambition de comprendre la nature, la portée et les fonctionnalités de la négociation dans le règlement des litiges transnationaux d’investissement. Negotiation is a fascinating instrument of Investment Law, versatile and rich in legal content. The systematic study of negotiation in Investment Law reveals that this institution is much more than just an instrument for reaching agreements. In fact, negotiation is everywhere. It is the only institution of Investment Law that is truly transversal, intervening in many layers of the relationship between investors and Host States. We can recognize the existence of negotiations from the very beginning of an investment process (the negotiation of a contract between the investor and the Host State), as well as negotiations over the course of the life and operation of an investment, and negotiations at the termination of a transnational investment project. Moreover, negotiation is an instrument that serves arbitral tribunal as element for the interpretation of the agreements, and the determination of the parties’ liability. The various roles of negotiation in Investment Law have certainly contributed to the evolution of international law. Nevertheless, negotiation remains an unknown institution to lawyers, regarding its nature, scope, uses and legal content. Investment law requires a thorough analysis of this institution and a structure that adapts to the transnational legal order. In this research, we will examine numerous contributions of negotiation to Investment Law: as a necessary mechanism for the conclusion of agreements that impact Investment Law; as a mandatory rule that it imposes specific behaviors on the parties in respect to the principle of good faith; as an instrument that serves international tribunals to determine the parties’ liability for their actions taken over the course of negotiations, and as an instrument to assist the justice system to construe contracts. Thus, the ambition of this research is to comprehend the nature, scope, and the features of negotiation in International Investment Law. La negociación es un instrumento fascinante de Derecho de las inversiones, a la vez versátil y rico en contenido legal. El estudio sistematizado de la negociación en el Derecho de las inversiones revela que esta institución es mucho más que un instrumento para alcanzar acuerdos. En realidad, la negociación está en todas partes en el derecho de las inversiones. Es laúnica institución verdaderamente transversal al Derecho de las inversiones, que interviene de varias formas en la relación entre inversionistas y los Estados receptores de inversión. Podemos constatar la existencia de las negociaciones desde el inicio de un proceso de inversión (en la negociación de un tratado bilateral deinversión, o de un contrato entre el inversionista y el Estado anfitrión), negociaciones durante la vida y la operación de una inversión y negociaciones encaminadas a la terminación o liquidación de la inversión transnacional. Resalta, además, que la negociación es un instrumento al servicio de la instancia jurisdiccional, que sirve a los árbitros en su tarea de interpretación de acuerdos, y a la determinación de la responsabilidad de las partes. Los diversos roles que presenta la negociación en el Derecho de las inversiones ciertamente han contribuido a la evolución del Derecho internacional. Sin embargo, la negociación sigue siendo una institución poco conocida por los juristas, especialmente en lo tocante a su naturaleza, alcance, usos y contenido legal. ElDerecho de las inversiones requiere de un análisis exhaustivo de esta institución, acompañado de una estructura que se adapte al orden legal transnacional.En esta investigación examinaremos las diversas contribuciones que hace la negociación al Derecho de las inversiones, a saber: se muestra como un mecanismoinevitable para concluir acuerdos que terminan contribuir en la evolución del Derecho de las inversiones; impone a las partes comportamientos específicos enrespeto del principio de la buena fe; es un instrumento para que los tribunales internacionales determinen la responsabilidad de las partes en razón de sus accionesdurante la fase de negociación y se constituye en un instrumento que asiste al sistema de justicia en la tarea de interpretar los acuerdos. La ambición de esta investigación no es otra cosa que comprehender la naturaleza, el alcance y la funcionalidad de la negociación en el Derecho internacional de las inversiones.
Keywords: Accord; Arbitrage; Arbitrage d'investissement; Arbitration; Bonne foi; Buena fe; Contenido jurídico; Contract interpretation; Contrahendo; Contrato; Derecho Internacional Público; Derecho de las Inversiones; Droit de l’investissement; Droit international; Duty to negotiate; Estoppel; Good faith; Interpretación de acuerdos; Interprétation de l’accord; Investissements étrangers; Investment Law; Investments; Justicia; Negociación; Negotiando; Negotiation; Negotiation agreement; Négociation; Négociations; Obligación de negociar; Obligation de négocier; Pacto de negociación; Pactum; Período de negociación; Public International Law; Transnacional; Transnational

Visão Contemporânea da Jurisdição Arbitral - Bellocchi, Marcio (Universidade de São Paulo, 2022)
A questão fundamental que está por detrás da investigação feita para elaboração deste estudo consiste em saber se a arbitragem é jurisdição. A pesquisa foi conduzida de forma analítica de molde a que conclusões fossem alcançadas no sentido de se saber até que ponto a arbitragem é mesmo jurisdição. É claro que, para que isso fosse feito, isto é, para que esse caminho fosse percorrido, o primeiro tema a ser tratado deveria ser, necessariamente, a própria jurisdição. Trata-se de um conceito construído pela cultura humana cujo conteúdo, exatamente por isso, variou ao longo da história. Seguiu-se a mesma abordagem no que diz respeito à arbitragem. Assim, o primeiro objetivo desta tese foi o de acompanhar a evolução do conceito de jurisdição, ao longo do tempo, como forma de composição de conflitos, desde o direito romano, até a atualidade. Foi explorado o caminho pelo qual passou a jurisdição, com o fim de se investigar por qual motivo, em determinado momento, se começou a afirmar, de modo peremptório, que a jurisdição seria uma atividade realizada exclusivamente pelo Estado. O segundo objetivo consistiu em analisar a arbitragem, pondo-a lado a lado com a jurisdição estatal, explorando-se os pontos que ambos os fenômenos apresentam em comum, assim como os que diferenciam essas duas formas de exercício do poder-dever de julgar. Por isso, foi objeto de investigação e reflexão uma outra função da jurisdição estatal, recentemente assumida de forma clara pela jurisdição estatal, que é a de contribuir para a criação do direito. Procurou-se identificar em que contexto e extensão isso pode acontecer, tanto na jurisdição do Estado, quanto na jurisdição contratada pelas partes. Em um terceiro momento deste estudo, colocamos luzes sobre determinados institutos do processo civil, desenvolvendo-os, também, no terreno do procedimento arbitral. Num quarto e último momento, nossas reflexões se voltaram para o problema de se saber até que ponto a arbitragem seria mesmo jurisdição, equivalente à jurisdição estatal, em todos os seus aspectos, em toda a sua extensão, seus limites e suas funções. The fundamental question behind the research done to prepare this paper is whether arbitration is jurisdiction. The research has been conducted in an analytical manner so that conclusions could be reached in order to know to what extent arbitration is even jurisdiction. For this to be done, the first topic to be addressed should necessarily be jurisdiction itself. This is a concept constructed by human culture whose content, precisely for this reason, has varied throughout history. The same approach has been followed about arbitration. Thus, the first aim of this thesis was to follow the evolution of the concept of jurisdiction, over time, as a form of dispute resolution, since Roman law, until today. Jurisdiction has been explored, to investigate why, at a certain point, it began to affirm, peremptorily, that jurisdiction would be an activity performed exclusively by the State. The second aim was to analyze arbitration, placing it side by side with State jurisdiction, exploring points that both: state and arbitral jurisdiction have in common, as well as those that differentiate these two forms of judging. Therefore, another function, recently clearly assumed by the state jurisdiction, which is to contribute to the creation of law, has been object of investigation and reflection. It was sought to identify in what context and extent this can happen, both in the State and arbitral jurisdiction. In a third moment of this study, we shed light on certain institutes of civil procedure, developing them, also, in the field of arbitration procedure. In a fourth and last moment, our reflections turned to the problem of knowing to what extent arbitration would even be jurisdiction, equivalent to the State jurisdiction, considering all its aspects, its extent, limits and functions.
Keywords: Arbitrage; Arbitragem; Arbitration; Creation; Criação; Jurisdiction; Jurisdição; Procedure; Processo

La notion de sentence arbitrale : étude de droit de l'arbitrage commercial - Merabti, Priscilla (Université Paris 1, 2022)
Qu’est-ce qu’une sentence arbitrale ? La sentence arbitrale est le résultat attendu par les parties qui se soumettent à une procédure arbitrale. Elle constitue le seul outil juridictionnel mis à la disposition de l’arbitre au cours d’un arbitrage. La sentence se voit revêtue d’un régime particulier, qui n’est pas ouvert aux autres types d’actes délivrés par l’arbitre, qui sont les ordonnances de procédures. La qualification en tant que sentence arbitrale d’une décision est donc une question primordiale, lorsqu’il est question d’arbitrage. La notion de sentence arbitrale n’est pas identique d’un droit à un autre et la définition française de la sentence arbitrale issue de l’arrêt Sardisud de la cour d’appel de Paris apporte son lot d’incertitudes en termes de qualification. En effet, la confrontation de cette définition à un certain nombre de cas d’objet d’étude suscite des interrogations. Ces interrogations poussent à l’analyse de chacun des critères permettant sa qualification, questionnant leur interprétation, mais aussi parfois leur nécessité. Certaines « zones grises » font naître des doutes de qualification de certaines décisions délivrées par l’arbitre en tant que sentence arbitrale : c’est le cas de la mesure provisoire, mais aussi de la sentence d’accord-parties. D’autres cas de figure posent des difficultés de qualification en deux temps, avec tout d’abord la question de la qualification de la procédure en tant qu’arbitrage et ensuite celle de la décision qui en découle en tant que sentence arbitrale. En effet, ces deux qualifications sont étroitement liées, d’une part puisque la sentence arbitrale ne peut exister sans arbitrage et d’autre part, car il existe une porosité des critères utilisés dans les définitions de l’arbitrage et de la sentence arbitrale. Ces difficultés de qualification en deux temps existent dans le cadre de la procédure d’arbitrage à deux degrés, la procédure devant un Dispute Adjudication Board en matière de construction, lors des procédures pré-arbitrales d’urgence, mais aussi lors d’une demande d’adaptation de contrat à un arbitre. L’étude de l’ensemble de ces cas de figure offre la possibilité de mettre à l’épreuve la définition actuelle de la sentence arbitrale, de souligner ses déficiences et de proposer une nouvelle approche de la notion de sentence arbitrale qui se décompose en deux propositions : d’une part, une interprétation plus élargie de certains critères utilisés dans la définition de la sentence arbitrale et d’autre part la disparition de certains critères qui apparaissent injustifiés.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitraje; Arbitral Awards; Arbitration; Arbitres (droit); Notion; Qualification; Sentence arbitrale

L’exécution des sentences arbitrales contre les personnes publiques de l’OHADA - Vodounon-Djegni, Comlan René (Université Côte d'Azur, 2022)
La thèse porte sur « L’exécution des sentences arbitrales contre les personnes publiques de l’OHADA ». Elle a pour but de démontrer comment mettre en œuvre ces sentences sans se heurter à l’immunité d’exécution des personnes qui en bénéficient. En effet, en l’absence d’une exception arbitrale, l’interdiction de l’exécution forcée et des mesures conservatoires à l’encontre de ces personnes semble s’étendre à l’exécution forcée des sentences arbitrales contre les personnes publiques de l’OHADA. Or, comme ces dernières, l’immunité d’exécution a également un fondement contractuel ; c’est une règle d’ordre public de protection à laquelle le bénéficiaire peut renoncer. Donc, son application ne serait requise que si son bénéficiaire n’y a pas renoncé. Mais, pour être valable, la renonciation à l’immunité d’exécution doit être expresse, au sens du droit international coutumier, dont fait partie la Convention des Nations Unies sur l’immunité juridictionnelle des Etats et de leurs biens du 2 décembre 2004, applicable en droit OHADA, pour raison de droit. Cette condition de validité de la renonciation pose le problème de l’efficacité des contrats soumis aux règles impératives du droit public ou des conventions et règlements d’arbitrage. Alors, faudrait-il envisager la réécriture des modèles habituels de conventions et règlements d’arbitrage pour y intégrer cette condition ? Cette approche garantirait l’effectivité des sentences arbitrales administratives, sur le fondement de la force obligatoire des contrats (Pacta sunt servenda) et de leur exécution de bonne foi. Aussi, pourrait-on renforcer cette renonciation par la mention de biens affectés à l’activité en cause ou à l’exécution de la sentence qui s’ensuivra sans lien avec l’activité qui y a donné lieu. En tout état de cause, l’immunité d’exécution ne s’oppose ni à l’identification des débiteurs des condamnations pécuniaires des personnes publiques, ni à l’exequatur des sentences arbitrales adm inistratives, ni même à l’exécution volontaire ou spontanée desdites sentences. Ainsi, en dépit de sa conception absolue ou stricte, l’immunité d’exécution de l’OHADA a des limites à l’égard des sentences arbitrales administratives.
Keywords: Administrative arbitration award; Arbitrage; Arbitrage (droit administratif); Arbitragem; Arbitration; Mandatory rules of public law; Organisation pour l'harmonisation en Afrique du droit des affaires; Personnes publiques; Renonciation à l’immunité d’exécution; Règles impératives du droit public; Sentence arbitrale administrative; Waiver of immunity from execution

İslam borçlar hukuku açısından ticari ihtilafların çözümünde 'Arabuluculuk' - Almasri, Raed (Ankara Üniversitesi, 2022)
Bu tez, anlaşmazlıkları çözmede arabuluculuk konusunu ele almaktadır. Arabuluculuk konusu ticari mali muamelelerdeki anlaşmazlıklar ile sınırlıdır. Dolayısıyla tez ailevi anlaşmazlıklardaki nafaka gibi diğer mali anlaşmazlıklara değinmemektedir. Tez konusu fıkhi açıdan ele alındığı için, dört fıkhi mezhebin konuyla ilgili görüşleri, mukayeseli olarak işlenmiş, mezhepler arasında ihtilaf ve ittifak edilen noktalar ele alınmış ve görüşler arasında tercih yapılarak ortaya konulmuştur. Tez; bir mukaddime, üç bölüm, bir sonuç ve kaynakçadan meydana gelmektedir. Mukaddime de tezin planı, fihrist ve içerik ele alınmıştır. Tezin birinci bölümünde; arabuluculuk kavramının tanımı ve meşruiyeti, ikinci bölümde; arabuluculuğun rükünleri ve arabuluculukla ilgili hükümler ve şartlar, üçüncü bölümde ise; arabuluculuğun sonuçları ve etkisi ele alınmıştır. The dissertation aims to cover the subject of mediation in dispute resolutions exclusively in commercial disputes. Therefore, the research does not cover mediation in other disputes such as domestic disputes even when it's related to financial matters such as alimony. The research also studies mediation in commercial disputes from a jurisprudential perspective. Hence the jurists' opinions are presented and analyzed in a comparative approach to show its similarities, differences and present a jurisprudential preference. The dissertation is presented in an introduction, three chapters, a conclusion followed by the list of references and resources. The introduction provides an insight into the research contents and methodology. The first chapter discuss the definition of mediations and its legitimacy. The second chapter tackle the main pillars of mediations and clarify its ruling and conditions. Finally, the third chapter view the results of mediations and its expected impacts.
Keywords: Arabuluculuk; Borçlar hukuku; Commercial disputes; Incompatibility; Islamic law; Law of obligations; Mediation; Ticari uyuşmazlıklar; Uyuşmazlık; İslam hukuku

Paradigm Shift in Investment Treaty Arbitration: Toward Stricter Control over the Qualifications and Conduct of Arbitrators - Kamalinejad, Hassan (University of Victoria, 2022)
There is a growing concern over the qualifications and social interactions of investment treaty arbitrators. The characteristics of this class of international adjudicators have significantly evolved over the past few decades. The contemporary arbitration panelist interacts within a broad and complex network of arbitration participants. Their patterns of social behavior both within the community of panelists and within the broader network of actors in arbitration proceedings have fundamentally reshaped the composition, dynamics and culture of the arbitration community. These new forms of relationships and patterns of conduct are new in the context of public international law. These have created unprecedented challenges to the investment treaty arbitration system. New manifestations of attributes and social behavior of panelists demonstrate inadequacies of the existing standards, rules and procedures that govern panelists. This study surveys problematic patterns of social behavior of investment treaty adjudicators and shows how certain instances of social behavior inevitably or potentially jeopardize the very foundations of the system. This research empirically examines the voting behavior of two distinct groups of party-appointed panelists, and the results reveal a relationship between appointments and the decision-making attitude of adjudicators. It further methodically maps the pool of ICSID panelists and answers the question ‘who are ICSID panelists?’ It reviews the evolution of the attributes of ICSID adjudicators, assesses the composition of the ICSID pool, and evaluates the social interactions of this group of investment treaty adjudicators. To address the challenges that investment treaty arbitration faces, a radical and multidimensional shift is occurring in the system. This transformation is directed towards greater control over the qualifications and conduct of adjudicators. These developments reconstruct the composition of the pool of adjudicators and influence how they interact with other actors in investment treaty arbitration proceedings. The ongoing reform progress indicates that the attributes and behavior of future investment treaty adjudicators would likely be different from the characteristics and conduct of the contemporary generation of panelists.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Code of conduct; ICSID; Impartiality; Investment treaties; Investment treaty arbitration; Investments; Permanent court system; Qualifications; State practice

الحق المعنوي للفنان العازف أو المؤدي في قانون الملكية الأدبية والفنية - دراسة مقارنة - - بعديد, دلال (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
يعتبر الفنان العازف أو المؤدي، الطائفة الوحيدة من أصحاب الحقوق المجاورة التي تتمتع بحقوق معنوية ومالية على أعماله. فالطابع الإبداعي الذي يكتسيه أداؤه يبرز شخصيته الأدبية والفنية، على خلاف أعمال أصحاب الحقوق المجاورة التي تتسم بالطابع الصناعي اولمادي. يتضمن الحق المعنوي جملة من الصلاحيات تمكن الفنان من الاستفادة من أعماله وحمايتها من مختلف أنواع الاعتداء. غير أنها وإن كانت تتشابه في البعض منها مع الحقوق المخولة للمؤلف لحماية مصنفات ه وشخصه، إلا أنها تختلف معها في البعض منها لاسيما الحق في تقرير النشر، والحق في السحب أو الندم، باعتبار أن التشريعات الوطنية الخاصة بالحقوق المجاورة والتي اعترف ت للفنان التمتّع بحق معنوي ، جاءت خالية من الإشارة إلى ذلك. لذا كان من الضروري تحديد مدى تمتع الفنان العازف بهذين الحقين، أمام الف ا رغ القانوني الذي أدى إلى مجادلات فقهية وتضا رب في الأحكام القضائية. L'artiste interprète ou exécutant est le seul des titulaires de droits voisins à bénéficier d’un droit moral et d’un droit patrimonial sur son interprétation. Le caractère original de sa prestation met en valeur sa personnalité littéraire et artistique, à l’inverse des oeuvres des titulaires de droits voisins qui se caractérisent par leur aspect industriel et matériel. Le droit moral dont dispose l'artiste-interprète, comprend un ensemble de prérogatives qui lui permettent de bénéficier de ses oeuvres et de les protéger contre les divers abus. Cependant, et bien qu’elles soient similaires, pour certaines d’entre elles, aux droits octroyés à l’auteur pour protéger son oeuvre et sa personne, elles se différencient de certains d’entre eux, en particulier le droit de divulgation et le droit de retrait ou de repentir, du fait que les législations nationales relatives aux droits voisins qui reconnaissent à l'artiste la jouissance d’un droit moral, sont dépourvues de toute référence à ce sujet. Dès lors, il était nécessaire de déterminer dans quelle mesure l'artiste-interprète jouit de ses deux droits, face au vide juridique qui a donné lieu à des controverses doctrinales et à des décisions de justice contradictoires. The artist, musician or performer, is the only one of the holders of related rights to benefit from a moral right and financial rights over his performance. The original character of his performance highlights his literary and artistic personality, unlike the works of holders of neighboring rights which are characterized by their industrial and material aspect. The moral rights available to the performer include a set of prerogatives that allow them to benefit from their works and protect them against various abuses. However, and although they are similar, for some of them, to the rights granted to the author to protect his work and his person, they are different from some of them, in particular the right of disclosure and the right of withdrawal or of repentance, due to the fact that national laws relating to neighboring rights which recognize the artist's enjoyment of a moral right, are devoid of any reference to this subject, Therefore, it was necessary to determine to what extent the performer enjoys both rights, in the face of the legal vacuum which has given rise to doctrinal controversies and contradictory court decisions.
Keywords: Arbitrage; Arbitration; Artist interpréter; Artist performer; Artiste exécutant; Artiste interprète; Contrefaçon; Counterfeiting; Droit moral; Intellectual property; International protection; Moral right; National protection; Piracy; Piratage; Propriedade intelectual; Propriété intellectuelle; Protection internationale; Protection nationale; Responsabilité; Responsibility

ال رقابة القضائية على أحكام ال ت حكيم دراسة مقارنة في القوانين العربية - زريفي, محمد (Université d'Oran 2 Mohamed Ben Ahmed, 2022)
إن كان التحكيم طريقا بديلا للقضاء في حسم المنازعات، فإن عملية التحكيم تحتاج لكي تكتمل أسباب فاعليتها وانفاذ أحكامها لتدخل قضاء الدولة باعتباره سلطة عامة، تملك قوة إل ا زم الخصوم بتنفيذ أحكام المحكمين. ومن باب المفارقة، أن هذه الرقابة القضائية على أحكام التحكيم، تؤدي إلى إقحام القاضي الوطني في ن ا زع، أستبعد منه مسبقا بإ ا ردة المتنازعين، إلا أن المفارقة ظاهرية، حيث أن دور القاضي يبقى منحص ا ر في رقابة مدى مطابقة الحكم التحكيميي لمبادئ أساسية، أتت على سبيل الحصر، دون أن يكون له فحص وقائع وموضوع الن ا زع. غير أن تحديد سلطة القاضي لي س مطلقة، فبناء على المقاربة الجديدة المبنية على نوع المصالح المطلوب حمايتها، كمعيار لتحديد درجة وشدة الرقابة المسلطة على حكم لتحكيم، يستطيع هذا الأخير، تعديل رقابته بين مشددة ومخففة . وعلى هذا الأساس، فإن غالبية القضاءات العربية تبنت موقفا وسطيا بين مذهبي التوسع والتضييق من نطاق رقابة المحاكم على حكم التحكيم الدولي، تماشيا مع متطلبات التجارة الدولية ومقتضيات مصالحها الوطنية . If arbitration is an alternative means of resolving disputes, the arbitration process needs, for the reasons of its effectiveness and the application of its provisions, the intervention of the judicial power of the State, in order to oblige the parties to carry out the arbitral awards. Paradoxically, this judicial review of arbitral awards leads to involving the national judge in a dispute, which was previously excluded by the will of the parties in dispute. However, this paradox is apparent, because the role of the national judge remains limited to the strict control of the compliance of the arbitration award with the basic principles enacted in an exclusive manner, without having to examine the facts and the subject of the dispute. However, this limitation of judicial power is not absolute, because on the basis of the new approach, based on the type of interests to be protected, as the criterion for determining the extent of the control exercised over an arbitral award, the latter can modulate its control between strict and attenuating. On this basis, the majority of Arab jurisdictions have adopted a middle position between the two tendencies, so-called maximalist control, and minimalist tendency of the jurisdictions' control over the international arbitration award, in accordance with the needs of international trade and the requirements of their interests. Si l'arbitrage est un moyen alternatif pour de résoudre les différends, le processus d'arbitrage a besoin, pour les raisons de son efficacité et l'application de ses dispositions de l'intervention du pouvoir judiciaire de l'État, afin d'obliger les parties d'exécuter les sentences arbitrales. Paradoxalement, ce contrôle judiciaire sur les sentences arbitrales conduit à impliquer le juge national dans un litige, qui en était auparavant exclu par la volonté des parties en litige. Toutefois, ce paradoxe est apparent, car le rôle du juge national reste limité au strict contrôle de la conformité la sentence arbitrale aux principes de base édicté d’une manière exclusive, sans avoir à examiner les faits et l'objet du litige. Cependant, cette limitation de pouvoir juge n'est pas absolue, car sur la base de la nouvelle approche, fondée sur le type d'intérêts à protéger, comme critère de détermination de l'étendue du contrôle exercé sur une sentence arbitrale, ce dernier peut moduler son contrôle entre strict et atténuant. Sur cette base, la majorité des juridictions arabes ont adopté une position médiane entre les deux tendances, contrôle dite maximaliste, et tendance minimaliste du contrôle des juridictions sur la sentence d'arbitrage international, conformément aux besoins du commerce international et aux exigences de leurs intérêts.
Keywords: Arbitrage international; Arbitration; Commerce international; Contrôle des juridictions; International Trade; International arbitration award; Sentence arbitrale